A comparative analysis of the informational efficiency of the fixed income market in seven European countries - Fernández Bariviera, Aurelio (2012)
This letter investigates the time-varying behavior of long memory in sovereign and corporate bond indices of seven European Union countries from July 1998 to November 2011. We compute the Hurst exponent and detect that the current financial crisis affects more the informational efficiency of the corporate bond market than the sovereign bond market. © 2012 Elsevier B.V.